(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with linguistic principles of morphology studying at secondary comprehensive school. The author describes the principle meanings of grammar theory in the Ukrainian language school course.